Legal Position of Underhand Agreements in Land Investment with Buyback Schemes in Indonesia - Sulistyanto, Bagus (UNISSULA, 2025)
This study examines the legal position of underhand agreements in land investment in Indonesia, particularly within buyback schemes that are increasingly used in practice. Although not executed before a notary, such agreements remain valid if they fulfill the essential elements of a contract under the Indonesian Civil Code. Using a normative legal approach supported by case studies, this research analyzes the validity, legal risks, and investor protection issues surrounding these informal transactions. The findings indicate that underhand agreements, while offering flexibility and lower costs, create vulnerabilities due to weak evidentiary value in disputes. Ambiguous buyback clauses and the absence of authentic documentation often hinder investors from reclaiming funds, generating legal uncertainty and escalating civil conflicts. Opportunistic behavior by landowners further exacerbates the imbalance of bargaining power. The legal urgency addressed in this study lies in the need for regulatory reform to strengthen legal certainty and investor protection in land investment. Recommendations include mandatory registration of buyback agreements, involvement of notarial services, and improved legal literacy for stakeholders. This study contributes to ongoing discussions on legal reform by emphasizing the balance between contractual freedom and equitable protection in Indonesia’s land investment sector.